2016
DOI: 10.1007/s00223-016-0225-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass and Strength are Significantly Improved in Mice Overexpressing Human WNT16 in Osteocytes

Abstract: Recently, we demonstrated that osteoblast-specific overexpression of human WNT16 increased both cortical and trabecular bone mass and structure in mice. To further identify the cell-specific role of Wnt16 in bone homeostasis, we created transgenic (TG) mice over-expressing human WNT16 in osteocytes using Dmp1 promoter (Dmp1-hWNT16 TG) on C57BL/6 (B6) background. We analyzed bone phenotypes and serum bone biomarkers, performed gene expression analysis and measured dynamic bone histomorphometry in Dmp1-hWNT16 TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…After having established the regulatory role of GCs on Wnt16 expression, we addressed whether Wnt16 is able to rescue GC-induced suppression of bone formation. Interestingly, single treatment of both, primary osteoblasts and mice did not significantly alter osteoblast function, indicating that short-term treatment with Wnt16 may not be sufficient to enhance osteoblast function in the same way as long-term exposure as in WNT16 overexpressing mice 36 , 37 . Similarly, osteoblasts derived from Wnt16KO mice did not show alterations in their differentiation capacity 34 However, co-treatment of osteoblasts with DEX and recombinant Wnt16 abrogated the GC-induced suppression of osteoblast function in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After having established the regulatory role of GCs on Wnt16 expression, we addressed whether Wnt16 is able to rescue GC-induced suppression of bone formation. Interestingly, single treatment of both, primary osteoblasts and mice did not significantly alter osteoblast function, indicating that short-term treatment with Wnt16 may not be sufficient to enhance osteoblast function in the same way as long-term exposure as in WNT16 overexpressing mice 36 , 37 . Similarly, osteoblasts derived from Wnt16KO mice did not show alterations in their differentiation capacity 34 However, co-treatment of osteoblasts with DEX and recombinant Wnt16 abrogated the GC-induced suppression of osteoblast function in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 98%
“…The regulatory role of Wnt16 on cortical bone and bone strength was further validated using global and osteoblast-lineage Wnt16 knock-out mice 32 , 34 , 35 , showing that osteoblast-derived Wnt16 inhibits osteoclastogenesis 34 . Overexpression of Wnt16 in osteoblasts or osteocytes led to higher cortical as well as trabecular bone mass in mice and caused an increase in bone formation compared to controls 36 , 37 suggesting that Wnt16 also promotes osteoblast differentiation and function, similar to other Wnt ligands 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple GWAS studies have shown that genetic variants of Wnt16 are associated with BMD and fracture risk [7,10,46]. Research by Imranul Alam et al showed that human Wnt16 overexpression in osteocytes influences trabecular and cortical bone mass, structure, and strength in mice; Wnt16 affects the quality and strength of cortical bone and trabecular bone; and this molecule can be used as a therapeutic intervention to treat osteoporosis or other low bone mass and high bone fragility disorders [47]. For the VEGF signaling pathway, inhibition of VEGF signaling pathway and angiogenesis has become a promising method in preclinical research in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple association signals mapping to the 7q31.31 locus have been consistently reported in GWAS of BMD of paediatric populations [17,[25][26][27][28]31] and adult populations [21,22,36,37]. There is considerable evidence that either WNT16 [38][39][40][41][42], CPED1 [39], ING3 [43] or FAM3C [44] are underlying the association signal. As conditional independent markers have been described in this locus (a phenomenon known as allelic heterogeneity) [25,26], it is even likely that all these genes are key factors in bone biology, as supported by a recent transcriptome-wide association study [45].…”
Section: Polygenic Basis Of Paediatric Fracturementioning
confidence: 89%